PENERAPAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR PKN SISWA KELAS III SD NEGERI 24 LUBUKLINGGAU - Octe, Legi Laura; Syaprizal, Syaprizal; Abadi, Candres (Primary Education Journal Silampari (PEJS), 2024)
This study aims to determine whether the scramble learning model on the learning outcomes of third grade Civics students of SD Negeri 24 Lubuklinggau significantly completed. The research design was in the form of a pseudo-experiment in the pre-test and post-test group category. The research was conducted at SD Negeri 24 Lubuklinggau with the population being third grade students. Sampling was done by random sampling. The data collection technique was done with a test technique consisting of 25 questions. The data collected was then analyzed using the Z-test. Based on the results of research and discussion, it can be concluded that the learning outcomes of Civics in class III SD Negeri 24 Lubuklinggau after the application of the picture and picture learning model is significantly complete. The average value of student learning outcomes for the pretest was 59.08, for the posttest it increased to 83.54 with the number of students who were complete also increased by 84.61%. While based on the results of hypothesis testing analysis obtained Zhitung > Ztabel = Zhitung (6.237) > Ztabel (1.64), thus the proposed hypothesis can be accepted, scramble learning model on student learning outcomes Civics Class III SD Negeri 24 Lubuklinggau significantly Completed. Keywords: Scramble, Learning Outcomes, Civics